The influence of crowd noise and size on fouls and home court advantage in the WNBA - Rubenstein, Kerianne Lawson; Gershon, Karly (Journal of Sports Research, 2025)
Large and loud crowds add to the intensity of a sporting event and impact player performance. A rowdy crowd can cause players and coaches, particularly those from the visiting team, to make mistakes or become frustrated, leading to more flagrant and technical fouls in basketball games. This article examines how crowd size, along with other factors that influence the noise level in the arena, correlates with flagrant and technical fouls in the Women’s National Basketball Association (WNBA). This article uses a fixed effects model with crowd size, as measured by the percentage of the arena that is full, as the variable of interest and fouls as the outcome variable. The model controls for the size of the arena and other game-specific characteristics. The results indicate that crowd size, and therefore crowd noise, is positively associated with flagrant fouls and technical fouls committed by coaches. This article also investigates how larger and louder crowds affect the home and away teams differently. The findings provide some evidence of a home court advantage in terms of technical fouls committed by coaches. This article contributes to the existing literature on how crowds can contribute to home court advantage but provides additional context by looking at fouls as an outcome variable.